A Case of Hemorrhagic Shock Caused by Epiploic Appendage Bleeding - Kawakami, Koji; Hirata, Yuichiro; Ono, Takeshi; Kato, Koji; Higa, Satoru; Nakachi, Hiromichi (Nihon Fukubu Kyukyu Igakkai Zasshi (Journal of Abdominal Emergency Medicine), 2019)
A 77-year-old male patient with a history of abdominal pain was transported to our emergency room in a shock state. Blood tests revealed anemia and evidence of prerenal renal failure. Abdominal CT showed bloody ascites and extravasation of contrast from the vicinity of the sigmoid colon. We made the diagnosis of intraabdominal hemorrhage from the sigmoid mesocolon, and undertook emergency surgery. At laparotomy, a large hematoma was found, and the source of the hemorrhage was the epiploic appendage of the sigmoid colon. The bleeding was controlled by ligature of the epiploic appendage, and the patient was transferred to his previous hospital on postoperative day 20. As far as we know, this is the first presented case from Japan of hemorrhage as the main manifestation of a epiploic appendage in the abdominal cavity.